Qcd Sum Rules for the G(KK*pi)(Q(2)) form factor - Holanda, L. B.; De Carvalho, RSM; Nielsen, M. (World Scientific Publ Co Pte Ltd, 2003)
The QCD Sum Rules have been used to evaluate the form factor in the vertex KK*pi. The method of QCD Sum Rules is based on the duality principle in which it is assumed that the hadrons can simultaneously be described in two levels: quarks and hadrons. This work showed that the, axial current, used to describe the meson K is not appropriated to study the form factor.